A percepção dos usuários das compras realizadas pelo setor público: estudo de caso na Universidade Federal de Goiás - Rodrigues, Camila Cardoso de Carvalho (2018)
The area of procurement is essential for the objectives of an organization. In the public sector, it is not different. The government procurement with efficiency will promote the good performance of the public financial, providing the operation of the activities of the public administration as well as their public politics. Therefore, it is necessary to verify those expenses, if they are bringing good results. And a way for that is to verify the perception that who use those procurement public. In that sense, the objective of this research was to analyze the procurement public by a public institution, under the perspective who users them and to propose an instrument that permit the continuous improvement of the expenses with public improvement. For the elaboration of the diagnosis, the bibliographical and documental research were used to know the characteristics of the institution in study, as well as the research with the survey to verify the users’ perception. The results were analyzed with base in the efficiency and in the dimensions of performance of the public procurement: quality, time, price, transparency and sustainability. As it was verified that the beginning phase of the process of procurement public influences the result directly, this work make as product a manual of proceeding for the requisition of procurement public that can possible procurement public with efficiency and improve the expectations that who uses them.